2021
DOI: 10.1097/corr.0000000000001736
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy Gunshot-induced Tibia Fractures: What Proportion Develop Complications?

Abstract: Background Gunshot injuries of the extremities are common in the United States, especially among people with nonfatal gunshot wounds. Controversy persists regarding the proper management for low-energy gunshot-induced fractures, likely stemming from varying reports on the likelihood of complications. There has yet to be published a study on a large cohort of patients with gunshot-induced tibia fractures on which to base our understanding of complications after this injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Additionally, the prolonged duration until complete soft tissue closure, the extended hospital stays, and the need for multiple surgeries and admissions, further emphasize the enduring impact and heightened burden of those injuries on the patients and on the already under-resourced and overburdened Gaza healthcare system [ 24 ]. We also identified a noteworthy non-union rate among patients (53.0%), which is notably higher than the estimated global range of 10–30% for non-union in open tibial fractures [ 25 28 ]. This can be attributed to the challenging healthcare environment in the Gaza Strip, where limited resources, including medical supplies, personnel, and infrastructure, often hinder the delivery of adequate care, especially in emergency situations [ 24 ].…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, the prolonged duration until complete soft tissue closure, the extended hospital stays, and the need for multiple surgeries and admissions, further emphasize the enduring impact and heightened burden of those injuries on the patients and on the already under-resourced and overburdened Gaza healthcare system [ 24 ]. We also identified a noteworthy non-union rate among patients (53.0%), which is notably higher than the estimated global range of 10–30% for non-union in open tibial fractures [ 25 28 ]. This can be attributed to the challenging healthcare environment in the Gaza Strip, where limited resources, including medical supplies, personnel, and infrastructure, often hinder the delivery of adequate care, especially in emergency situations [ 24 ].…”
Section: Discussionmentioning
confidence: 74%
“…Lee and colleagues [4] support this concept, particularly in patients who underwent a deep debridement as defined by the authors. Indeed, Lee et al found loss of soft tissue was associated with a higher risk of deep infection [4].…”
Section: Where Are We Now?mentioning
confidence: 92%
“…For example, researchers could limit the study population to those who potentially have a higher risk of complications. Lee and colleagues [4] found that patients with gunshot wounds who had deep debridement after tibia fracture have a higher risk for infection; this high-risk population may be suitable for randomization in studies looking to mitigate a deep infection in view of higher complication rates, which should allow smaller numbers to be analyzed based on power calculations.…”
Section: How Do We Get There?mentioning
confidence: 99%
See 2 more Smart Citations